Voices of Long-Term Care Workers Elder Care in the Time of COVID-19 and Beyond - Freidus, Andrea (Berghahn Books, 2024)
There were many challenges, successes, and concerns in providing long-term care to older adults during the COVID-19 pandemic. Looking at central North Carolina, the authors highlight the implications of providing long-term care to older Americans, with an emphasis on the importance of communication, resilience of staff, and value of human infrastructure.Based on extensive interviews, this collection of essays reflects on the participants' individual experiences and represents the voices of staff and caregivers working in long-term residential care communities, in-home and community-based programs, as well as regional aging service providers and advocates.